Detailed construction techniques and their effect on the directing discourse semantics A critical reading in the samples of Nizar Qabbani's poetry - Mohiedain, Eftekhar Salaim (Journal of Arabic Language Sciences and Literature, 2024)
This research deals with the detailed construction techniques and their effect on the directing discourse semantics in a group of poetic samples by Nizar Qabbani from a textual critical perspective. Because of its great importance in the formation of semantics and poetic meanings, and directing them within the literary text, and these techniques are: the technique of detail after summarization, the technique of formulaic frequency, and the technique of repetitive framing.In its methodology, the research relied on reading various models of Qabbani's poetry, representing various stages of his poetic experience, an analytical and investigative reading. Poetic cohesion, highlighting the expressive functions of the text.
Keywords: construction techniques; detailed; directing discourse semantics; poetic meanings; criticism; Poetic cohesion